2014
DOI: 10.3390/nu6114760
|View full text |Cite
|
Sign up to set email alerts
|

n-3 Polyunsaturated Fatty Acids and Mechanisms to Mitigate Inflammatory Paracrine Signaling in Obesity-Associated Breast Cancer

Abstract: Globally, the prevalence of obesity is increasing which subsequently increases the risk of the development of obesity-related chronic diseases. Low-grade chronic inflammation and dysregulated adipose tissue inflammatory mediator/adipokine secretion are well-established in obesity, and these factors increase the risk of developing inflammation-associated cancer. Breast cancer is of particular interest given that increased inflammation within the subcutaneous mammary adipose tissue depot can alter the local tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 252 publications
(462 reference statements)
1
30
0
Order By: Relevance
“…The pathways implicated in the response include decreased Akt activation [ 5 ], increased neutral sphingomyelinase activity [ 20 ], increased BRCA levels [ 21 ], and increased PTEN levels [ 22 ]. GPCR-independent mechanisms have been reviewed [ 23 ]. To date, there is little information available concerning the roles of FFARs in breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The pathways implicated in the response include decreased Akt activation [ 5 ], increased neutral sphingomyelinase activity [ 20 ], increased BRCA levels [ 21 ], and increased PTEN levels [ 22 ]. GPCR-independent mechanisms have been reviewed [ 23 ]. To date, there is little information available concerning the roles of FFARs in breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, studies have shown that n‐3 PUFAs can reduce monocyte chemoattractant protein‐1 (MCP‐1) levels in visceral adipose tissue, contributing to a reduction of adipose tissue inflammation in obesity. Also, n‐3 PUFA is able to inhibit NFκB activation, promoting a decrease of TNFα, IL‐1β, and IL‐6 . In another study, authors found a suppression of IL‐6 secretion in adipose cells after 48 h of treatment with the omega‐3 fatty acid docosahexaenoic acid .…”
Section: Discussionmentioning
confidence: 93%
“…In breast cancer cells, DHA strongly reduces cell viability and DNA synthesis and promotes cell death via apoptosis [9]. The proposed mechanisms include the ability of DHA to decrease the total amount of and to alter the size of lipid rafts in breast cancer cells, disrupting membrane signaling involved in the regulation of cell survival and proliferation and sensitizing cells to apoptosis [64]. The protective effects of n-3 PUFA result in reduced breast cancer incidence, growth, multiplicity and metastasis in rodent models of breast cancer [64].…”
Section: Discussionmentioning
confidence: 99%
“…The proposed mechanisms include the ability of DHA to decrease the total amount of and to alter the size of lipid rafts in breast cancer cells, disrupting membrane signaling involved in the regulation of cell survival and proliferation and sensitizing cells to apoptosis [64]. The protective effects of n-3 PUFA result in reduced breast cancer incidence, growth, multiplicity and metastasis in rodent models of breast cancer [64]. Furthermore, in a mouse model of obese postmenopausal breast cancer, n-3 PUFA supplementation reduced mammary adipose tissue inflammation and markers of inflammatory M1 macrophage infiltration [65] which were associated with reduced tumor burden, indicating that the inflammatory microenvironment promotes tumorigenesis and that n-3 PUFA directly antagonizes this process.…”
Section: Discussionmentioning
confidence: 99%